A pilot study on physiological relaxation and enhanced work performance by volatile organic compounds emitted from Kagawa hinoki (Chamaecyparis obtusa) interior walls - Fumi Kishida; Kazuki Tani; Taisuke Nakashima; Fadilla Zennifa; Akiko Isa; Noboru Fujimoto; Koki Fujita; Ryuma Taki; Hiroo Yasutomi; Naotoshi Yasumori; Kuniyoshi Shimizu (Journal of Wood Science)
Abstract Since ancient times, Japanese cypress timber (Chamaecyparis obtusa; 'hinoki' in Japanese) has been highly valued in Japan. Because of its beautiful color and fragrance, this timber has been widely used as houses and furniture materials. Scientific evidence on the effect of the usage of hinokis’ timber especially from Kagawa’s area as a building material toward human psychophysiological response has yet to be reported. The current study examined participants’ psychophysiological responses to volatile organic compounds (VOCs) generated by hinoki interior walls growing in Kagawa Prefecture, Japan. This timber was reported to have a relaxing effect toward the participants, and this study discovered that inhaling air containing VOCs emitted by Kagawa hinoki interior walls increased parasympathetic nervous activity during resting periods between arithmetic tasks. When compared to a control condition, the participants' performance on a calculation test improved dramatically in the hinoki condition. These findings suggest that VOCs released by Kagawa hinoki walls influence the autonomic nervous system, emotions, and work performance. This study not only proved Kagawa hinoki fragrance’s potential to boost human working speed, but it also newly confirmed the fragrance's ability to increase parasympathetic nervous system activity while at rest. This study also discovered that the enhanced working speed is caused by a part of the neurological underpinning for heightened arousal in the brain. As a result, this study concluded that the aroma of cypress can have physiological effects that change over time, hence optimizing individuals’ behavior at work and at rest.